# Solving linear equations.

• Apr 13th 2008, 05:31 AM
Mymble
Solving linear equations.
How can I solve this?

((5p-4)/6) - ((2p+3)/2) = 7

In my text book it says the answer is p = -55 but I've tried and can't get this.

Thanks.
• Apr 13th 2008, 05:35 AM
Moo
Hello,

Put the fractions in the left hand side of the equality on the same denominator (6).

Then, do the same for 7. 7=42/6 and multiply both sides by 6.

After that, you may solve it like a normal equation... Can you show a bit of your work ? To see if you're going the right way :)
• Apr 13th 2008, 05:41 AM
Mymble
Quote:

Originally Posted by Moo
Hello,

Put the fractions in the left hand side of the equality on the same denominator (6).

Then, do the same for 7. 7=42/6 and multiply both sides by 6.

After that, you may solve it like a normal equation... Can you show a bit of your work ? To see if you're going the right way :)

I keep ending up with p = -37

I did...

((5p-4)/6) - ((6p+9)/6) = 42/6

5p-4-6p+9=42 (multiplied by 6)

-p+5=42

-p=37

(Worried)
• Apr 13th 2008, 05:46 AM
mr fantastic
Quote:

Originally Posted by Mymble
I keep ending up with p = -37

I did...

((5p-4)/6) - ((6p+9)/6) = 42/6

5p-4- (6p+9) =42 (multiplied by 6) Mr F says: USE BRACKETS!

5p - 4 - 6p - 9 = 42 etc.

-p+5=42

-p=37

(Worried)

Ahhhhh the benefits of showing working. What you should have done is in red. The really important thing is in blue!
• Apr 13th 2008, 05:53 AM
Mymble
Quote:

Originally Posted by Mymble
I keep ending up with p = -37

I did...

((5p-4)/6) - ((6p+9)/6) = 42/6

5p-4-6p+9=42 (multiplied by 6)

-p+5=42

-p=37

(Worried)

Quote:

Originally Posted by mr fantastic
Ahhhhh the benefits of showing working. What you should have done is in red. The really important thing is in blue!

Oh!
I think I understand that...
Because it's minus (6p+9) the +9 becomes -9?

So...
((5p-4)/6) - ((6p+9)/6) = 42/6

5p-4-6p-9=42

-p+=55

-p=55

p=-55

Thanks so much!
• Apr 13th 2008, 05:53 AM
Moo
That's it ^^

The - sign is distributed into the parenthesis ;)

When you substract : -(a+b) this means you substract a AND b, so it's like -a-b
• Apr 13th 2008, 06:00 AM
mr fantastic
Quote:

Originally Posted by Mymble
Oh!
I think I understand that...
Because it's minus (6p+9) the +9 becomes -9?

So...
((5p-4)/6) - ((6p+9)/6) = 42/6

5p-4-6p-9=42

-p+=55

-p=55

p=-55

Thanks so much!

(Clapping)

ps: And thankyou for your lovely manners!
• Apr 13th 2008, 06:02 AM
Mymble
Thankyou very much for your help both of you.

Sorry if it seemed a silly mistake.
• Apr 13th 2008, 06:04 AM
mr fantastic
Quote:

Originally Posted by Mymble
Thankyou very much for your help both of you.

Sorry if it seemed a silly mistake.

As long as you learn from it, it's certainly not silly.